2006
DOI: 10.1007/s00403-006-0715-8
|View full text |Cite
|
Sign up to set email alerts
|

Blood urokinase plasminogen activator system in chronic urticaria

Abstract: The evidence gathered has pointed to the fibrinolytic system, which apart from its major role in hemostasis may also be involved in inflammatory and immune processes. To understand better the role of fibrinolysis in urticaria, we measured plasma levels of the urokinase system associated molecules such as urokinase-type plasminogen activator (uPA), its soluble receptor (suPAR; CD87) and an inhibitor, plasminogen activator inhibitor type 1 (PAI-1) activity in chronic urticaria (CU) patients. Plasma was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…29,30 However, urokinase-type plasminogen activator (uPA), suPAR and plasminogen activator inhibitor-1 were not elevated in one study in CSU patients. 31 We add to these previous observations our finding of increased PAP-complex levels in CSU compared to healthy controls. There is a large bout of evidence demonstrating that activation of the fibrinolytic system and contact system go hand in hand.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…29,30 However, urokinase-type plasminogen activator (uPA), suPAR and plasminogen activator inhibitor-1 were not elevated in one study in CSU patients. 31 We add to these previous observations our finding of increased PAP-complex levels in CSU compared to healthy controls. There is a large bout of evidence demonstrating that activation of the fibrinolytic system and contact system go hand in hand.…”
Section: Discussionmentioning
confidence: 58%
“…The fibrin degradation product D‐dimer is associated with CSU, and it correlates with disease severity and antihistamine‐resistant urticaria . However, urokinase‐type plasminogen activator (uPA), suPAR and plasminogen activator inhibitor‐1 were not elevated in one study in CSU patients . We add to these previous observations our finding of increased PAP‐complex levels in CSU compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In CSU and/or DPU sera, 11 different markers were investigated in nine different studies. TG2, 53 VEGF, 55,56 endostatin, 57 thrombospondin‐1 (TSP‐1), 57 substance P, 58 and chitinase‐3‐like protein 1 (YKL‐40) 59 were described upregulated whilst controversially, other studies (n=4) showed normal regulation of VEGF or VEGF1 and VEGF2, 56,60 vascular endothelial growth factor receptor (VEGFR), 56 substance P, 61 and the urokinase‐type plasminogen activator (u‐PA)/plasminogen activator inhibitor‐1 (PAI‐1)/soluble receptor of urokinase‐type plasminogen activator (suPAR)system 62 …”
Section: Resultsmentioning
confidence: 99%
“…12 Moreover, CU patients showing positive response to ASST had plasma profile of the urokinase system-associated proteins, which was not markedly different as compared with CU patients with negative ASST as well as healthy subjects, suggesting that systemic fibrinolysis may not be involved in chronic urticaria. 13 …”
Section: Discussionmentioning
confidence: 99%